Análise da herança do DNA do Trypanosoma cruzi em parentais e progênies de chagásicos de famílias de São Felipe – Bahia - Santos, Eduardo José dos (2019)
The Trypanosoma cruzi, etiologic agent of Chagas disease is a flagellate protozoan transmitted by insect bugs (Reduvidae:Triatomine) to humans and wild mammals. The T. cruzi contains DNA in the nucleus (nDNA) and in the mitochondrion (kDNA). The kinetoplastid protozoan comprises maxicircles and and minicircles kDNA network sequences that integrate in the host’s cell genome. Insertional integrations of kDNA sequences bear high affinity to retrotransposable LINE-1 randomly distributed in the genome of somatic and germ line cells, and, thus generate an increasing diversity due to recombination and reshuffling. However, the profiles of kDNA integrations into the human genome in different Brazilian Ecosystems are unknown. In this regard, the ratio of transfer of T. cruzi minicircles sequences into the human genome was south. The study consisted of analyses of 36 members of two families from São Felipe-Bahia where Chagas disease is endemic. The study showed that 22% (8/36) families’ members had the diagnoses of the disease by immunofluorescence (IF) and enzyme-linked immunosorbant assay (ELISA). Yet, the PCR assays showed 61% (22/36) of families’ members had kDNA and nDNA assays positive for the T. cruzi infection. In order to detect the kDNA integration sites in the human genome, a tpTAIL-PCR (Targeted Primer Thermal Assymetric Interlaced-PCR), which consisted in combination of primers derived from T. cruzi minicircle conserved sequence with human LINE-1 sequence derived primers, was employed. The amplicon sequences obtained were subjected to homology analyses in Blast software. The hybrid kDNA-human DNA sequences revealed lateral and vertical transfer of T. cruzi minicircles into the genome of Chagas parents and progeny. Unravel of dynamics of mutations contributes to define variable profiles of kDNA minicircle sequence insertions into the human genome at different Ecosystems.